Cardiac radiation dose predicts survival in esophageal squamous cell carcinoma treated by definitive concurrent chemotherapy and intensity modulated radiotherapy - Tzu-Hui Pao (Radiation Oncology, 2020)
Abstract Background The prognostic significance of cardiac radiation dose in esophageal cancer after definitive concurrent chemoradiotherapy (CCRT) remains largely unknown. We aimed to investigate the association between cardiac dose-volume parameters and overall survival (OS) in esophageal squamous cell carcinoma (ESCC) after definitive CCRT. Methods One hundred and twenty-one ESCC patients undergoing definitive CCRT with intensity modulated radiotherapy technique between 2008 and 2018 were reviewed. Cardiac dose-volume parameters were calculated. Survival of patients and cumulative incidence of adverse events were estimated by the Kaplan–Meier method and compared between groups by the log-rank test. The prognostic significance of cardiac dose-volume parameters was determined with multivariate Cox proportional hazards regression analysis. Results Median follow-up was 16.2 months (range, 4.3–109.3). Median OS was 18.4 months. Heart V5, V10, and V20 were independent prognostic factors of OS. Median OS was longer for patients with heart V5 ≤ 94.3% (24.7 vs. 16.3 months, p = 0.0025), heart V10 ≤ 86.4% (24.8 vs. 16.9 months, p = 0.0041), and heart V20 ≤ 76.9% (20.0 vs. 17.2 months, p = 0.047). Lower cumulative incidence of symptomatic cardiac adverse events was observed among patients with heart V5 ≤ 94.3% (p = 0.017), heart V10 ≤ 86.4% (p = 0.02), and heart V20 ≤ 76.9% (p = 0.0057). Patients without symptomatic cardiac adverse events had a higher 3-year OS rate (33.8% vs. 0%, p = 0.03). Conclusions Cardiac radiation dose inversely correlated with survival in ESCC after definitive CCRT. Radiation dose to the heart should be minimized.